HUBUNGAN WAKTU PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DENGAN STATUS GIZI PADA BAYI USIA 6 – 24 BULAN DI WILAYAH KERJA PUSKESMAS KALIBAGOR KABUPATEN BANYUMAS - Linda Yanti; Kiki Octaviani NH (Viva Medika, 2012)
Background: Infants who have aged more than 6 months should be given extra food to meet theirnutritional needs in addition to breastmilk, or so-called complementary feeding (MP-ASI). Giving MPASI at the right time and with the kind of age-appropriate complementary feeding can have a positiveimpact on the nutritional status of children. Nutritional status is a state body as a result of foodconsumption and utilization of nutrients. Objective: To determine the relationship of the timing of complementary feeding and nutritional status ininfants aged 6-24 months in Puskesmas Kalibagor Banyumas in 2012. Methods: This study is a retrospective descriptive correlation approach. This study uses primary dataobtained using a checklist sheet about the timing of complementary feeding and nutritional status ofinfants aged 6-24 months. Samples are taken with the baby's mother 95 cluster random samplingtechnique. Results: Mothers in Puskesmas Kalibagor Banyumas in 2012 largely provide complementary feedingwhen infants aged <6 months as many as 56 people (58.9%). The nutritional status of infants aged 6-24months in Puskesmas Kalibagor Banyumas in 2012 mostly in the good category were 83 infants (87.4%). Conclusion: There is a relationship between the timing of complementary feeding and nutritional statusin infants aged 6-24 months in Puskesmas Kalibagor Banyumas In 2012 obtained p = 0.002 smaller than= 0.05. Keywords: Delivery of complementary feeding, nutritional status of infants aged 6-24 months